2022
DOI: 10.21203/rs.3.rs-1620232/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ubiquitous Superconducting Diode Effect in Superconductor Thin Films

Abstract: A superconductor exhibiting a polarity-dependent critical current is of fundamental as well as technological interest, because the superconducting (SC) layer can then admit a perfect dissipationless transmission along one direction while offering a large resistance along the opposite, leading to a phenomenon called SC diode effect or rectification. Here we demonstrate that SC diode effects are ubiquitous in superconductors and observable in a large variety of settings. Controllable via an out-of-plane magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…When superconductivity breaks from the edge of the sample, the sign of Q should change depending on which end of the sample the superconductivity starts to break from. First, we verified the contribution of asymmetric edges [ 14 ] by examining the reproducibility of Q . As shown in Figure S4 (Supporting Information), we confirmed that the values of | Q | are reproduced at ≈40%, and the sign of the zero‐field SDE does not change.…”
Section: Resultsmentioning
confidence: 99%
“…When superconductivity breaks from the edge of the sample, the sign of Q should change depending on which end of the sample the superconductivity starts to break from. First, we verified the contribution of asymmetric edges [ 14 ] by examining the reproducibility of Q . As shown in Figure S4 (Supporting Information), we confirmed that the values of | Q | are reproduced at ≈40%, and the sign of the zero‐field SDE does not change.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the observation of non-reciprocity in the critical current of superconductors, known as the superconducting diode effect (SDE) [1][2][3], has brought attention to this phenomenon for its potential to achieve dissipationless electronics. Following the initial observations, extensive work has been done to show the signature of SDE in different bulk materials [4][5][6][7][8]. This diode effect was also observed and thoroughly studied in Josephson junctions [9][10][11][12][13][14][15][16] (first in the context of the anomalous Josephson effect [17][18][19][20][21]) and even in the absence of an applied magnetic field [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, it has been realized that higher superconducting diode efficiency can be achieved in properly designed nanostructures in which the time-reversal symmetry is broken via trapped fluxes or an external magnetic field. However, a magnetic field is often undesired for integrating the devices in superconducting circuits. In this work, we rectify this problem by creating superconducting diodes which can operate at zero external magnetic field and achieve efficiency approaching 100%.…”
mentioning
confidence: 99%